Design and flow characterization of an indraft supersonic wind tunnel for scramjet testing - Teeter, Spencer J., author; Dumitrache, Ciprian, advisor; Windom, Bret, committee member; Bradley, Thomas, committee member (Colorado State University. Libraries, 2024)
This thesis describes the Colorado State University supersonic wind tunnel design, manufacture, assembly, and validation. The overarching goal of this research is to develop a ground testing platform for studying airbreathing hypersonic propulsion systems. Problems of interest include design of isolators, fuel injection systems, ignition and flame stabilization, shock-boundary layer interaction, and aero-thermo-elastic interactions in scramjet vehicles. An indraft-type tunnel was chosen for its simplicity, low capital investment, and low power requirement. Its main features are large windows for advanced optical flow diagnostics, modular experimental mounting system, cycle time under 15 minutes, and adjustable size up to 5.25" x 5.25" x 25". The bulk of this thesis research focuses on flow characterization using a Mach 2.5 nozzle and a test section of 5.25" x 1.57". To this effect, we determined the Mach number using shockwave schlieren and stagnation pressure measurements over longitudinal and transverse scans in the tunnel test section. Experiments show that steady-state flow consistently develops in 0.5 seconds at a uniform Mach 2.4 at the entrance of the test section decreasing to 1.5 at the exit. Nozzle outflow and shot-to-shot Mach number variation was low, while measurement deviation increased near the test section walls and exit due to boundary layer growth. By studying phenomena such as fuel mixing, ignition, and flame stability at high Mach numbers inside of a supersonic wind tunnel, research at the CSU's Aerospace Propulsion and Diagnostics Laboratory seeks to overcome the limitations of current scramjet technologies.
Keywords: propulsion; supersonic; wind tunnel; scramjet; aerodynamic; vacuum